Reader Response Perspective: Aspect of Character Education Values for Student in Lamongan Folklore - Widyaiswara, Tiara; Luthfiyati, Dian; Setyaningrum, Riya Risqi; Rohmah, Abidatur (Language Circle: Journal of Language and Literature, 2023)
This research aims to discover the responses of student in Lamongan folklore character education values. The folklore is the title Panji Laras Liris and Mbok Rondo Barang Danureksa, which was famous as the Lamongan legendries for a banning marriages between men from Lamongan and women from Kediri and prohibition for eating catfish. Most of in several Lamongan part is belief about this folklore. This research employed descriptive qualitative research methods, using data collection technique are observed the student in reader respons after read the folklore, and choose from ten students in C class in 9th at one of the Junior High Schools in Turi. Based on the results from interviews and reader responses, several factors impact the reader's manifestation of social function after reading literary works, including the knowledge of literature, reading experience, and individual attitudes toward daily life to face the milenials era.